Aunps/go Coated U-shape Polished Smf Based Localized Spr Sensor For Musta’mal Water Identification - Nur Zahirah Ahmad Khirri; Wan Maisarah Mukhtar; Razman Mohd Halim; Affa Rozana Abdul Rashid; Nur Athirah Mohd Taib (PENERBIT UniMAP (UniMAP PRESS), 2024)
International Journal of Nanoelectronics and Materials (IJNeaM) Volume 16 Special Issue Page (73-86)